Strong tough gels for 3D tissue constructs. Issue 1622 (2014) - Calvert, Paul; in het Panhuis, Marc; Spinks, Geoffrey; Gorkin, Robert; Stevens, Leo; Bakarich, Shannon E.; Balding, Paul; Kirchmajer, Damian M.
ABSTRACT: The mechanical characteristics of ionic-covalent entanglement hydrogels consisting of combinations of the biopolymers gellan gum and kappa-carrageenan, and the synthetic polymers polyacrylamide and an epoxy amine were investigated. Compression testing showed that these gels exhibited "double network" behavior, i.e. strong tough gels.